Local Cultural Transformation in the Development of Law Based on Religious Principles - Abrari, Achmad; Nailulfari, Fardati; Mohamed Alehirish, Mustafa Hamed (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This research explores implementing local cultural values ​​and religious principles to support forming fair laws relevant to community needs and contribute to sustainable legal development in Indonesia. Using the literature review system method, this research analyzes various literature and data related to local culture, religious principles, and the legal system in Indonesia. The research results show that local cultural values, such as cooperation, deliberation, and respect for community rights, play an essential role in creating laws that are more adaptive and responsive to the social context. In addition, integrating religious principles, such as justice, benefit, and balance, provides a strong moral foundation without ignoring cultural and religious plurality. This transformation supports social justice and builds a sustainable legal system. In conclusion, recognizing and harmonizing artistic and spiritual values ​​in the Indonesian legal system can create inclusive and relevant regulations for a multicultural society and become a central pillar in national legal reform.